Productive Time of Women and Water Supply in Ijumu, Local Government Area, Kogi State, Nigeria (Global Journal of Human-Social Science, 2010)
The study assessed productive time of women and water supply in Ijumu L.G.A. of Kogi state, Nigeria. Two hundred questionnaires were administered in the LGA and 32 socio-economic variables were generated altogether. Principal component analysis and stepwise regression analysis were used to interpret the data. The result of the principal components reduced the 32 variables to seven orthogonal components. The factor defining variables underlying the explanation are: water borne diseases, marital status and distances to the nearest water points. Others are: number of days lost to treatment, family size, and age of respondent. These components offered 95.5% explanation to the variance. Furthermore, the result of the stepwise regression analysis showed that all variables entered into the equation and they together contributed 98% to the equation. The paper concludes that water use characteristics at the household level differ from place to place and therefore there is need for caution on result interpolation. The paper recommends the need for provision of more public water points in the local government area in other to improve access to water supply and release more time for productive activities in the community. This results calls for further studies particularly on water chemistry, gender, poverty and on determination of efficient distances to water points Keywords-productive time,